Optical+Near-IR Analysis of a Newly Confirmed Einstein Ring at z ∼ 1 from the Kilo-Degree Survey: Dark Matter Fraction, Total and Dark Matter Density Slope, and Initial Mass Function - Rui Li; Nicola R. Napolitano; Giuseppe D’Ago; Vyacheslav N. Shalyapin; Kai Zhu; Xiaotong Guo; Ran Li; Léon V. E. Koopmans; Chiara Spiniello; Crescenzo Tortora; Francesco La Barbera; Haicheng Feng; et al. (The Astrophysical Journal Letters)
We report the spectroscopic confirmation of a bright blue Einstein ring in the Kilo-Degree Survey (KiDS) footprint: the Einstein “blue eye.” Spectroscopic data from X-Shooter at the Very Large Telescope (VLT) show that the lens is a typical early-type galaxy (ETG) at z _l = 0.9906, while the background source is a Ly α emitter at z _s = 2.823. The reference lens modeling was performed on a high-resolution Y- band adaptive-optics image from HAWK-I at VLT. Assuming a singular isothermal ellipsoid total mass density profile, we inferred an Einstein radius R _Ein = 10.47 ± 0.06 kpc. The average slope of the total mass density inside the Einstein radius, as determined by a joint analysis of lensing and isotropic Jeans equations, is ${γ }_{tot}=2.1{4}_{-0.07}^{+0.06}$ , showing no systematic deviation from the slopes of lower-redshift galaxies. This can be the evidence of ETGs developing through dry mergers plus moderate dissipationless accretion. Stellar population analysis with eight-band ( gri ZYJHK _s ) photometries from KiDS and VIKING shows that the total stellar mass of the lens is M * = (3.95 ± 0.35) × 10 ^11 M _⊙ (Salpeter initial mass function (IMF)), implying a dark matter fraction inside the effective radius of f _DM = 0.307 ± 0.151. We finally explored the dark matter halo slope and found a strong degeneracy with the dynamic stellar mass. Dark matter adiabatic contraction is needed to explain the posterior distribution of the slope, unless an IMF heavier than Salpeter is assumed.